2022
DOI: 10.1155/2022/6435774
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Biofilm Formation and Antibiotic Resistance and Adherence Genes in Staphylococcus aureus Strains Isolated from Raw Cow Milk in Shahrekord, Iran

Abstract: The production of biofilms by S. aureus contributes significantly to treatment failures. The present study aims to establish the relationship between biofilm formation and antibiotic resistance and adhesion genes in Staphylococcus aureus strains isolated from raw cow milk in Shahrekord, Iran. A total of 90 samples of raw cow’s milk were collected. Presumptive S. aureus strains were obtained using Baird-Parker plates after enrichment in tryptone soy broth, and final colonies were selected from brain heart infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
2
1
0
Order By: Relevance
“…Phenotypic assessment of the antibiotic resistance showed that penicillin was found to be dealing with the most resistance, as 48.49% of the isolates were found to be resistant to it, followed by cefoxitin at 44.33%, tetracycline at 35.84%, gentamicin at 30.18% and vancomycin as 20.75%. The highest incidence of penicillin resistance is also reported by several other studies [38–40]. A similar order of phenotypic antibiotic resistance was observed by Mekuria et al [41] and was correlated with increased levels of use, overuse and misuse of antibiotics in farming either as treatment or prophylactic approach.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Phenotypic assessment of the antibiotic resistance showed that penicillin was found to be dealing with the most resistance, as 48.49% of the isolates were found to be resistant to it, followed by cefoxitin at 44.33%, tetracycline at 35.84%, gentamicin at 30.18% and vancomycin as 20.75%. The highest incidence of penicillin resistance is also reported by several other studies [38–40]. A similar order of phenotypic antibiotic resistance was observed by Mekuria et al [41] and was correlated with increased levels of use, overuse and misuse of antibiotics in farming either as treatment or prophylactic approach.…”
Section: Discussionsupporting
confidence: 81%
“…The highest level of mecA gene presence can be explained by the overlapping mechanism of action displayed by mecA and blaZ genes for the expression of resistance. A somewhat similar order of gene harbouring was also reported by Pajohesh et al [38], but he reported the highest percentage of blaZ gene, followed by others, which is different from our study. The prevalence of MRSA having mecA gene isolated from different livestock species has been documented in the previous studies conducted in goats [28], bovines [14], sheep [40] and equines [43] in different regions of Pakistan, which are in the range of the current study findings of MRSA.…”
Section: Discussionsupporting
confidence: 67%
“…12 out of 50 highly resistant strains were selected for biofilm formation. Results confirmed that antibiotic resistance is associated with biofilm formation [ 13 , 14 ], therefore, MDR-PA was selected for biofilm formation . P. aeruginosa culture was adjusted to McFarland standard turbidity of 1.…”
Section: Methodsmentioning
confidence: 81%